Elucidating the consumption and CO2 emissions of fossil fuels and low-carbon energy in the United States using Lotka–Volterra models. (1st April 2016) - Tsai, Bi-Huei; Chang, Chih-Jen; Chang, Chun-Hsien
Abstract: By using the Lotka–Volterra model, this work examines for the first time the feasibility of using low-carbon energy to reduce fossil fuel consumption in the United States and, ultimately, to decrease CO2 emissions. The research sample in this work consists of data on energy consumption and CO2 emissions in the United States. Parameter estimation results reveal that although the consumption of low-carbon energy increases the consumption of fossil fuels, the latter does not affect the former. Low-carbon energy usage, including nuclear energy and solar photovoltaic power, increases fossil fuel consumption because the entire lifetime of a nuclear or solar energy facility, from the construction of electricity plants to decommissioning, consumes tremendous amounts of fossil fuels. This result verifies the infeasibility of low-carbon energy to replace fossil fuels under the current mining technology, electricity generation skills and governmental policy in the United States and explains why the United States refused to become a signatory of the Kyoto Protocol. Equilibrium analysis results indicate that the annual consumption of fossil fuels will ultimately exceed that of low-carbon energy by 461%. Since our proposed Lotka–Volterra model accurately predicts the consumption and CO2 emission of different energy sources, this work contributes to the energy policies. Highlights: Our Lotka–Volterra model accurately predicts consumption of different energy sources. We find the current infeasibility of using low-carbon energy to reduce fossil fuels. The set-up of nuclear and solar plants increases fossil fuel usage in the U.S. The consumption of fossil fuels will exceed that of low-carbon energy by 435%. United States government prefers economic development over environmental protection.